2016
DOI: 10.1159/000452592
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of KIM-1 and NGAL as Early Indicators for Assessment of Gentamycin-Induced Nephrotoxicity <b><i>In Vivo</i></b> and <b><i>In Vitro</i></b>

Abstract: Background/Aims: The aminolycoside Gentamicin is a widely used antibiotic, applied in equine medicine. Despite its clinical use, concerns remain regarding the potential toxic side-effects, such as nephrotoxicity. Early detection of renal damage is critical in preclinical drug development. This study was aimed to determine whether kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) may be early indicators in the assessment of Gentamycin-induced nephrotoxicity. Methods: In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…In addition to these traditional serum biochemical markers of renal injury, kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) are considered as more sensitive and reliable biomarkers [25,26]. Previous studies have shown that the elevation of KIM-1 and NGAL is prior to the obvious renal tubule damage and the increments of serum creatinine (SCr) and blood urea nitrogen (BUN) levels [40]. Our results showed that the BUN, serum Creatinine, cystatin C, KIM-1 and NGAL were all significantly increased in the animals treated with APAP, indicating an acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these traditional serum biochemical markers of renal injury, kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) are considered as more sensitive and reliable biomarkers [25,26]. Previous studies have shown that the elevation of KIM-1 and NGAL is prior to the obvious renal tubule damage and the increments of serum creatinine (SCr) and blood urea nitrogen (BUN) levels [40]. Our results showed that the BUN, serum Creatinine, cystatin C, KIM-1 and NGAL were all significantly increased in the animals treated with APAP, indicating an acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that urinary KIM1 concentration is a more sensitive and specific readout of in vivo kidney injury in rats and humans than SCr and BUN led to US Food and Drug Administration (FDA) and European Medicines Agency (EMA) approval of KIM1 as one of seven biomarkers to be used in addition to SCr and BUN for monitoring drug-induced nephrotoxicity in preclinical trials 7679 . However, KIM1 has not performed as well in in vitro models, with a number of studies of primary proximal tubule cells or cell lines being unable to consistently detect significant differences in KIM1 expression between controls and cultures exposed to nephrotoxicants 8083 . These inconsistent findings might suggest that additional cell types are required within the organ for KIM1 expression to be induced or that deficits exist in the in vitro cell models with respect to their cellular identity and/or response to injury.…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%
“…The utility of urinary NGAL as a clinical biomarker of AKI is, however, limited by the finding that inflammation affects NGAL levels 78,9799 . NGAL is expressed at relatively high levels in proximal tubule cells in vitro, which may indicate the poor phenotype retention of proximal tubule cells when cultured using standard techniques as NGAL is not upregulated in mouse or rat proximal tubules following injury in vivo 6,82,83 . NGAL might be useful as a marker of distal tubule and collecting duct injury in vitro, although this possibility has not been extensively investigated.…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%
“…Owing to the poor sensitivity and specificity of these traditional markers, new indicators are required for a more accurate and early detection of kidney damage associated with the side effects of NSAIDs . In renal tissue injuries, many protein products such as neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) appear in the blood and may serve as new biomarkers for the early detection of acute kidney injury (AKI) (Ozer et al, 2010;Luo et al, 2016). NGAL, a small protein from the lipocalin family, is expressed exclusively in the tubular epithelium of the distal nephron and is released by tubular epithelial cells during AKI (Zhao et al, 2010).…”
Section: Acta Veterinaria Hungarica 67 2019mentioning
confidence: 99%